Students Interest And Usefulness Of Fieldwork Approaches To History - Salleh, Muhamad Johdhi; Ali, Hairuddin Mohd (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2009)
It is very exciting that history in the Integrated Cmriculum forSecondary School (ICSS) has been included as one of the core subjects inthe lower and upper secondary levels of Malaysian schools. These subjectsare officially included in the time table of the ordinary, religious, science,vocational and technical schools in the country. One of the most importantand effective methods introduced in the teaching and learning of historyis a fieldwork approaches, particularly a site visit. Since history is acompulsory subject, it is necessary to study and analyse the ICSS historycurriculum to see i f it really could achieve the objectives of the syllabus,successfully imparting knowledge and develop interest among studentsin the subject. The study involved about eight hundred students of selectedsecondary schools in the states of Perak and Terengganu. Instrimentsused were questionnaire and interview which were conducted with theselected respondents. The analysis of the study were presented inpercentage by using six Likert scale responses. The study shows that historyfieldwork contain many usefulness such as to develop, spark/ stimulate,motivate, investigate, prove, gain social experience, social sldUs, buildteacher-student relation, teaching-learning method, and fulfil NationalCurriculum. Moreover, the effective used of history fieldwork can enhancestudent interest in developing the country towards the advancement offirst class mind of human capital of Malaysian. It is hoped that the findingwill enlighten teachers and students in the learning of history in the ICSStowards achieving the stipulated aspiration, especially 1-Malaysia.